2017
DOI: 10.1002/cctc.201601420
|View full text |Cite
|
Sign up to set email alerts
|

Direct C3‐Arylation of 2 H‐Indazole Derivatives with Aryl Bromides by using Low Loading of a Phosphine‐free Palladium Catalyst

Abstract: The palladium‐catalyzed direct arylation of 2 H‐indazoles with aryl bromides for the preparation of 3‐aryl‐2 H‐indazoles was found to proceed in high yields when using only 0.5–0.1 mol % Pd(OAc)2 catalyst and KOAc as inexpensive base. A wide variety of electron‐deficient and electron‐rich aryl bromides and also heteroaryl bromides has been successfully employed. Both electron‐withdrawing and electron‐donating substituents on the 2 H‐indazoles are also tolerated. Moreover, the reaction can be performed in the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Recently, we reported a C3-direct arylation of 2 H 7-azaindazoles in water using Pd­(PPh 3 ) 2 Cl 2 as a catalyst and PPh 3 as a ligand (Scheme ). Later, Doucet and his group reported a phosphine free C3-arylation of 2 H -indazoles in DMA using 5 mol % of Pd­(OAc) 2 as a catalyst . Very recently, Popowycz and Lavrard reported C3-arylation of 1 H 7-azaindazoles under similar conditions previously developed by the Yu group using Pd­(phen) 2 (PF 6 ) 2 as a catalyst in the presence of Cs 2 CO 3 in toluene at 160 °C for 72 h…”
mentioning
confidence: 80%
“…Recently, we reported a C3-direct arylation of 2 H 7-azaindazoles in water using Pd­(PPh 3 ) 2 Cl 2 as a catalyst and PPh 3 as a ligand (Scheme ). Later, Doucet and his group reported a phosphine free C3-arylation of 2 H -indazoles in DMA using 5 mol % of Pd­(OAc) 2 as a catalyst . Very recently, Popowycz and Lavrard reported C3-arylation of 1 H 7-azaindazoles under similar conditions previously developed by the Yu group using Pd­(phen) 2 (PF 6 ) 2 as a catalyst in the presence of Cs 2 CO 3 in toluene at 160 °C for 72 h…”
mentioning
confidence: 80%
“…Belkessam et al reported C-3 arylation of 2benzyl-2H-indazole derivatives (28 a) with aryl bromides by using 0.5-0.1 mol% of phosphine-free palladium catalyst, Pd(OAc) 2 and an inexpensive base KOAc in DMA or CPME solvent at 120-150°C temperature to produce C-3 arylated 2H-indazoles 28 b (Scheme 28). [88] High yields (up to 90%) were obtained from bromobenzenes having electron-withdrawing groups as well as electron releasing groups at paraand meta-positions. Surprisingly, strongly electronrich 4-N,N-dimethylaniline produced less than 10% of the desired product.…”
Section: Arylationmentioning
confidence: 99%
“…as the base; this kinetic study actually showed that the reaction in CPME was the slowest, albeit it was complete after only 2 h. 218 More interesting was instead a following study reported in 2017: in this case, Doucet's group reported a C3 regioselective direct C-H bond arylation of 2H-indazoles with aryl bromides, carried out under ligand-free conditions with a low loading (0.1-0.5 mol%) of Pd(OAc) 2 as the catalyst and KOAc as the base; although DMA was used in most of these reactions, some examples with CPE were also reported, demonstrating it to be a suitable alternative to DMA. 226 Finally, in 2018 an extended study of direct C-H bond arylation reaction of heteroarenes with aryl bromides, performed in many sustainable solvents (including CPME) in combination with the presence of Pd/C as a recoverable and reusable catalyst, was reported by the same authors in order to develop highly eco-friendly protocols for direct C-H bond arylations (for more details, see section 2.1.2). 33 In addition to the significant contribution provided by Doucet's group, other interesting studies on the use of CPME as a sustainable solvent for direct C-H bond arylation of heteroarenes have been recently reported.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Biomassderive...mentioning
confidence: 99%